Proactivity routines: The role of social processes in how employees self-initiate change - Vough, H.; Bindl, U.; Parker, Sharon (Plenum Publishing Corporation, 2017)
Proactive work behaviors are self-initiated, future-focused actions aimed at bringing about changes to work processes in organizations. Such behaviors occur within the social context of work. The extant literature that has focused on the role of social context for proactivity has focused on social context as an overall input or output of proactivity. However, in this article we argue that the process of engaging in proactive work behavior (proactive goal-striving) may also be a function of the social context in which it occurs. Based on qualitative data from 39 call center employees in an energy-supply company, we find that in a context characterized by standardized work procedures, proactive goal-striving can occur through a proactivity routine – a socially constructed and accepted pattern of action by which employees initiate and achieve changes to work processes, with the support of managers and colleagues. Our findings point to the need to view proactive work behaviors at a higher level of analysis than the individual in order to identify shared routines for engaging in proactivity, as well as how multiple actors coordinate their efforts in the process of achieving individually-generated proactive goals.